1990
DOI: 10.1093/infdis/162.1.115
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Spectrum of Endophthalmitis: Incidence, Predisposing Factors, and Features Influencing Outcome

Abstract: Endophthalmitis is a virulent ocular inflammation typically developing suddenly and progressing rapidly. To better understand the incidence and factors predisposing to infection and influencing outcome, records of 114 patients with endophthalmitis hospitalized at one institution from 1980 to 1986 were reviewed. An infectious origin was confirmed in 79 patients (69%). The most common pathogens included staphylococcal species (Staphylococcus epidermidis, 33 cases; Staphylococcus aureus, 8 cases), streptococci (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
0
15

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(122 citation statements)
references
References 29 publications
3
104
0
15
Order By: Relevance
“…1 Also in the same period, in Scotland, 2 a hospital infection control team reported more acute PE than expected after cataract surgery, according to the normal incidence. 3 Among the many risk factors involved in the PE pathogenesis, [4][5][6][7][8][9][10][11] it is difficult to assess the weight of climatic influence; however, as conjunctival bacteria are the main source of contamination in cataract surgery, 12,13 it is quite logical to expect that the prevalence of conjunctival bacteria determines the prevalence of the infectious PE. Today, the world-wide use of povidona iodine solution as a preoperative prophylaxis in cataract extraction 14 could provide homogeneity in the kind of bacteria that produce PE all over the world, which was impossible to detect when a great number of different prophylactic techniques were used.…”
Section: Introductionmentioning
confidence: 99%
“…1 Also in the same period, in Scotland, 2 a hospital infection control team reported more acute PE than expected after cataract surgery, according to the normal incidence. 3 Among the many risk factors involved in the PE pathogenesis, [4][5][6][7][8][9][10][11] it is difficult to assess the weight of climatic influence; however, as conjunctival bacteria are the main source of contamination in cataract surgery, 12,13 it is quite logical to expect that the prevalence of conjunctival bacteria determines the prevalence of the infectious PE. Today, the world-wide use of povidona iodine solution as a preoperative prophylaxis in cataract extraction 14 could provide homogeneity in the kind of bacteria that produce PE all over the world, which was impossible to detect when a great number of different prophylactic techniques were used.…”
Section: Introductionmentioning
confidence: 99%
“…1 The underlying medical conditions of susceptible hosts include diabetes mellitus, intravenous drug abuse, cardiac valvular abnormality, 2 malignancy, and immune-compromised patients. Mowat et al 3 suggested the defect in the chemotaxis function of leukocytes in poorly controlled diabetic patients, as this case, probably makes such patients more susceptible to bacterial infection.…”
Section: Commentsmentioning
confidence: 99%
“…Sir, Metastatic choroidal melanoma to the ipsilateral orbit 7 years after enucleation Metastasis of choroidal melanoma to the contralateral orbit is rare. 1 Only one case with bilateral orbital involvement has been previously reported. 2 To our knowledge, we present the first case of choroidal melanoma metastasis to the ipsilateral orbit, 7 years after enucleation.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Owing to its urgent nature, empirical combination of antibiotics with coverage against both Grampositive and Gram-negative organisms are commonly employed. 2,3 Frequently used regimens include combination of vancomycin and aminoglycosides, or vancomycin with ceftazidime.…”
Section: Introductionmentioning
confidence: 99%